Ancient peat and apple extracts supplementation may improve strength and power adaptations in resistance trained men. Issue 1 (December 2016) - Joy, Jordan; Vogel, Roxanne; Moon, Jordan; Falcone, Paul; Mosman, Matt; Pietrzkowski, Zbigniew; Reyes, Tania; Kim, Michael
Abstract Background Increased cellular ATP levels have the potential to enhance athletic performance. A proprietary blend of ancient peat and apple extracts has been supposed to increase ATP production. Therefore, the purpose of this investigation was to determine the effects of this supplement on athletic performance when used during 12 weeks of supervised, periodized resistance training. Methods Twenty-five healthy, resistance-trained, male subjects completed this study. Subjects supplemented once daily with either 1 serving (150 mg) of a proprietary blend of ancient peat and apple extract (TRT) or an equal-volume, visually-identical placebo (PLA) daily. Supervised resistance training consisted of 8 weeks of daily undulating periodized training followed by a 2 week overreach and a 2 week taper phase. Strength was determined using 1-repetition-maximum (1RM) testing in the barbell back squat, bench press (BP), and deadlift exercises. Peak power and peak velocity were determined during BP at 30 % 1RM and vertical jump tests as well as a 30s Wingate test, which also provided relative power (watt:mass) Results A group x time interaction was present for squat 1RM, deadlift 1RM, and vertical jump peak power and peak velocity. Squat and deadlift 1RM increased in TRT versus PLA from pre to post. Vertical jump peak velocity increased in TRT versus PLA from pre to week 10 as did vertical jump peak power, which also increased from pre to post. Wingate peak power and watt:mass tended to favor TRT. Conclusions Supplementing with ancient peat and apple extract while participating in periodized resistance training may enhance performance adaptations. Trial Registration ClinicalTrials.gov registration ID:NCT02819219, retrospectively registered on 6/29/2016